COMPARATIVE INVESTIGATION ON THE ANATOMICAL, PHYSICAL AND CHEMICAL CHARACTERISTICS OF ZIZIPHUS SPINA - CHRISTI (L.) WILD FROM TWO REGION IN IRAN - Hossein Familian (Regional Information Center for Science and Technology (RICeST), 2003)
Ziziphus spina- christi of the family Rhamnaceae is widely distributed especially in the southern region of Iran and considered as one of the most drought - resistant sub species of the country. This investigation is the first attempt to study wood properties of this species, in order to contribute to a better understanding of it. It seems necessary to recognize the best utilization of this wood that are potentially available and easy to caltivate in Iran.The results of this study revealed that Ziziphus spina - christi is a diffuse - porous with pores round to oval, dense, hard and fine - textured wood. The length of vessel elements is medium, and the diameter relative high, few vessels per unit area and the type of perforation plates is simple. Parenchyma scanty paratracheal, vasicentric and rarely aliform. Libriform fibers length medium, thin to thick - walled. Rays 1-2 cells wide with medium length and not visible with nakedeye, crystals are common in most rays. In this species also percentages of cellulose and lignin are high but ash and extractive soluble in acetone content was found to be low.